Essential role for the putative S6 inner pore region in the activation gating of the human TRPA1 channel - Benedikt, Jan; Samad, Abdul; Ettrich, Rudiger; Teisinger, Jan; Vlachova, Viktorie (Biochimica et biophysica acta, 2009)
The ankyrin transient receptor potential channel TRPA1 is a sensory neuron-specific channel that is gated by various proalgesic agents such as allyl isothiocyanate (AITC), deep cooling or highly depolarizing voltages. How these disparate stimuli converge on the channel protein to open/close its ion-conducting pore is unknown. We identify several residues within the S6 inner pore-forming region of human TRPA1 that contribute to AITC and voltage-dependent gating. Alanine substitution in the conserved mid-S6 proline (P949A) strongly affected the activation/deactivation and ion permeation. The P949A was functionally restored by substitution with a glycine but not by the introduction of a proline at positions -1, -2 or +1, which indicates that P949 is structurally required for the normal functioning of the TRPA1 channel. Mutation N954A generated a constitutively open phenotype, suggesting a role in stabilizing the closed conformation. Alanine substitutions in the distal GXXXG motif decreased the relative permeability of the channel for Ca(2+) and strongly affected its activation/deactivation properties, indicating that the distal G962 stabilizes the open conformation. G958, on the other hand, provides additional tuning leading to decreased channel activity. Together these findings provide functional support for the critical role of the putative inner pore region in controlling the conformational changes that determine the transitions between the open and close states of the TRPA1 channel.
Keywords: Ion Channel Gating; Calcium; mutace; Nerve Tissue Proteins; TRPA1 Cation Channel; Electrophysiology; vápník; gating iontového kanálu; proteiny nervové tkáně; Food Preservatives; kationtové kanály TRP; Transient Receptor Potential Channels; Amino Acid Substitution; molekulární modely; isothiokyanatany; Models, Molecular; potravinářské konzervační látky; elektrofyziologie; lidé; Humans; substituce aminokyselin; Isothiocyanates; kationtový kanál TRPA1; Calcium Channels; Mutation; vápníkové kanály